2010
DOI: 10.1002/ijc.25021
|View full text |Cite
|
Sign up to set email alerts
|

Premature mortality due to cancer in Japan, 1995 and 2005

Abstract: To better understand premature mortality due to cancer, we estimated years of life lost (YLL) and average years of life lost (AYLL) due to cancer for the years 1995 and 2005, based on data from the Vital Statistic of Japan. In men, we identified a total of 159,623 cancer deaths in 1995 and 196,603 Results showed that cancer of the stomach, colorectum, liver and lung were the most frequent cancers in both sexes in both 1995 and 2005 and responsible for a remarkable number of YLL. Further, AYLL was greatest fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Consistent with those in previous publications [8, 9, 17, 18], the findings of the current analysis show that, on average, people with CNS cancer lost as many as 23 years of life among men and 27 years among women in 1980. Although their lifespan was prolonged in recent years, patients with CNS cancers still lost 21 years of life among men and 23 years among women in 2010.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with those in previous publications [8, 9, 17, 18], the findings of the current analysis show that, on average, people with CNS cancer lost as many as 23 years of life among men and 27 years among women in 1980. Although their lifespan was prolonged in recent years, patients with CNS cancers still lost 21 years of life among men and 23 years among women in 2010.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the most commonly reported statistics, such as incidence and mortality rates, may not fully reflect the burden of loss due to mortality. We were recently inspired by “life lost” measures, proposed in the Global Burden of Disease project [3-7], that described the impact of premature mortality among the Japanese population [8]. We observed that Japanese patients with CNS cancers lost the largest proportion of their lifespan relative to other cancer patients [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies in Japan, AYLL demonstrated a negative effect of breast cancer on lifespan in individual patients compared with other cancers. Stomach, liver and lung cancer in women, for instance, had AYLL of about 15-16 years, but breast cancer had AYLL of about 25 years (Pham et al 2009(Pham et al , 2010. The results from our study also showed that breast cancer patients in Japan have, however, benefited from a decline in AYLL, as indicated by a 3.6-year decrease in this variable at the end of the study period.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, the low utilization rate of cancer screening is another important problem for the Japanese health policy. For example, the rates of 2007 were 32.5%, 27.5%, for stomach and colon (male), and 25.3%, 22.7%, 20.3% 8) . Both local and central government are making their effort to increase the utilization rate; i.e., distribution of free ticket for cancer screening, cancer screening program for weekend and holidays, PR activities via mass medias.…”
Section: Health Statisticsmentioning
confidence: 99%